Aligning regional carbon neutrality pathways with national climate goals: An integrated analytical framework - Li Zhang; Mingyu Li; Zhe Zhang; Linyan Li; Jin Yuan; Shuying Zhu; Huili Wang; Min Jia; Jianhui Ruan; Lingyun Pang; Yingying Gu; Shu Ye; et al. (Environmental Science and Ecotechnology)
Under national carbon neutrality targets, energy-producing regions hold significant responsibilities for reducing emissions. Given the diverse economic, industrial, and resource profiles of these regions, tailored strategies are essential for designing regional emission pathways. Currently, a systematic analysis that simultaneously integrates broader national climate objectives and regional heterogeneity is lacking, hindering the formulation of localized roadmaps. To address this gap, we propose an integrated analytical framework combing top-down and bottom-up approaches. It considers macro-level constraints (socio-economic development) and micro-level feasibility (renewable energy potential and forest carbon sinks), incorporating diverse regional characteristics such as resource endowment, energy consumption patterns, and industrial structures. We apply this approach to an energy-producing region in central China. Our analysis highlights the need for a clean energy transition that maintains energy security and meets growing electricity demands. By 2060, wind and solar power are projected to account for 87% of electricity generation, representing a substantial shift from the current fossil-fuel-dependent structure. Significant reductions in greenhouse gas emissions can be achieved by optimizing the energy structure, enforcing production controls, and deploying advanced technologies across industry, transportation, and buildings. Additionally, enhancing carbon removal strategies will further support emission reduction targets. This framework demonstrates the feasibility of achieving climate objectives in fossil-fuel-dependent regions, providing strategic guidance for integrating regional traits into national decarbonization plans.